Prolotherapy Perineural Injection in Carpal Tunnel Syndrome with Bifid Median Nerve: A Case Report - Tresna Angga Basunanda; Arfano Januar Sangkai (Universitas Airlangga, 2022)
Background: Carpal tunnel syndrome (CTS) is a common neuropathy condition caused by entrapment of the median nerve. Perineural injection therapy with 5% dextrose or prolotherapy becoming a common method for treating carpal tunnel syndrome. Although it is effective, some anatomical variaton of the median nerve could effect the outcome of the prolotherapy in CTS. Case Report: A 43-year-old woman suffered from diurnal, nocturnal numbness and paraesthesia of the first, second, third and radial surface in the fourth finger of the right hand. She also complained pain in the same area with the VAS score of 8, and muscle weakness. Physical examination showed positive Tinel’s sign, Phalen’s sign and Durkan’s compression test. The Boston questionnare score showed a symptom average of 3.27 and a difficulty average of 3.25. USG examination showed that the patient had a bifid median nerve anatomy variaton. Discussion: Variation of median nerve branches has been reported as one of the prevalence of median nerve entraptment. In this case, a bifid median nerve variation was found through the USG imaging. Prolotherapy has been reported to be an effective method to treat carpal tunnel syndrome. But the bifid median nerve could affect the effectiveness of prolotherapy injection. Conclusion: In the case of a bifid median nerve, it is necessary to modify the injection technique so it would be more able to reach the whole of the bifid median nerve.